Retail Green Sukuk in Indonesia: Toward A Maqashid Approach - Khalilurrahman Khalilurrahman; Husni Mubarrak (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
Recent global trends include an increase in demand for sustainable development goals (SDGs) and green sukuk programs. The initiative has gained prominence due to the severe effects of climate change, global warming, and other environmental issues. With its green bond and green sukuk framework, Indonesia has endeavored to mitigate this effect. In response, the Indonesian government has issued Sukuk Tabungan (ST), which is designed to finance green projects. This article will examine the structure and performance of the Sukuk al-Wakalah contract, as well as the Maqashid method used to determine the mashlahah and priority level of Sukuk Tabungan, using the library research method and descriptive analysis. The study's findings indicate that Sukuk Tabungan could contribute to the achievement of the Sustainable Development Goals (SDGs) because it is designed in accordance with maqashid, which avoids Sharia-compliant practices in order to perform mashlahah. Even though it has a lower coupon rate and is of a smaller size than Sukuk Ritel, it has a high likelihood of being issued because its proceeds will be used exclusively to finance green projects in order to accelerate the Sustainable Development Goals. In addition, the objective of sukuk al Wakalah issuance appears to fall within the imperative level or dharuriyat of the Maqashid framework due to its five targeted projects, in accordance with the Islamic legal maxims